Analisis Resepsi Khalayak Terhadap Makna Muallaf Pada Iklan Online Bukalapak “A Stranger – A Ramadan Story” - Delya, Alfira Nanda; Sakuri, Anggy Aglevia; Sugiharto, Clarissa Erine (Universitas Al Azhar Indonesia, 2022)
As digital technologies dramatically reshape industry after industry, the selection of media for advertising is increasingly diverse. Online media is one of the mainstream media which is currently used as a tool for advertising with the aim of promoting a product widely and easily accessible to anyone with an internet connection. One of the companies that often advertise through online media is Bukalapak, which is one of the largest online marketplaces in Indonesia. This study aims to identify the audience's interpretation of the meaning of